2019
DOI: 10.4314/mejs.v10i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tillage and Intercropping as a Means to Increase Yield and Financial Return in the Drylands of Tigray, northern Ethiopia: A Case Study under Rainfed and Irrigation Conditions

Abstract: Intensive tillage is a major sustainability concern in cereal dominated cropping systems in the drylands of Tigray, Ethiopia. Hence, on-farm trials were conducted to investigate the yield and economic advantage of reduced tillage and intercropping for two seasons. A factorial experiment in a complete randomized block design was carried out at Adigudom located in Hintalo-Wajirat district in South-Eastern Tigray in 2014 (rain-fed) and 2015 (irrigated). The experiment consisted of four tillage frequencies (zero, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition to this, zero tilled sole maize had a yield advantage over similarly managed crops with conventional tillage systems [68,46]. Generally reduced tillage with maize soya bean intercrop is the best alternative for resource-poor farmers [64].…”
Section: Soya Bean Crop Biomass and Grain Yieldmentioning
confidence: 99%
“…In addition to this, zero tilled sole maize had a yield advantage over similarly managed crops with conventional tillage systems [68,46]. Generally reduced tillage with maize soya bean intercrop is the best alternative for resource-poor farmers [64].…”
Section: Soya Bean Crop Biomass and Grain Yieldmentioning
confidence: 99%
“…The area devoted to faba bean is also estimated to be 0.5 million ha, making up 30% of the total area coverage given for grain legumes [ 27 ]. The intercropping systems in northern Ethiopia comprise cereals with cereals, cereals with legumes, and trees with annual crops [ 28 ]. However, continuous adoption of improved maize varieties in the last three decades has changed on farms genetic diversity, increasingly leading to the growth of genetically homogeneous maize varieties.…”
Section: Introductionmentioning
confidence: 99%
“…After conducting research for four consecutive cropping seasons in the study area, Kiboi et al 14 reported no significant difference in yields between conservation and conventional tillage systems. This could be attributed to the long period required for yield increment under conservation tillage 15 . Thus, there is a need to incorporate soil fertility inputs and assess their effect on crop productivity over a longer term under conservation strategies.…”
Section: Introductionmentioning
confidence: 99%